2020
DOI: 10.13106/jafeb.2020.vol7.no10.359
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Human Capital and Innovative Entrepreneurial Capabilities of Tour Operators: Evidence from Andaman Coast, Thailand

Abstract: research for the grant. Also, my appreciation goes to all participants who dedicatedly involved throughout my research processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
6
0
5
Order By: Relevance
“…Tran (2011) stated that for tourism development, human resources for tourism have a great influence on sustainable development; human resources here are understood as human resources directly serving the tourism industry such as employees working in tourism businesses and also officials working in tourism authorities in the locality. The same view is seen in Maia et al (2005), Nguyen et al (2019), andHareeBin (2020).…”
Section: Tourism Resources (Tn)supporting
confidence: 68%
“…Tran (2011) stated that for tourism development, human resources for tourism have a great influence on sustainable development; human resources here are understood as human resources directly serving the tourism industry such as employees working in tourism businesses and also officials working in tourism authorities in the locality. The same view is seen in Maia et al (2005), Nguyen et al (2019), andHareeBin (2020).…”
Section: Tourism Resources (Tn)supporting
confidence: 68%
“…They are involved in the changing market. Under the marketing environment, seeking information from the required market on the customers' products and services makes the organization adjust and accept innovative data for applying and developing the innovation [53,54]. In return, Akbari et al [55] concluded that the innovative performance factors for organizational performance consisted of Quality, Quantity, Time, and Costs.…”
Section: Organizational Performancementioning
confidence: 99%
“…La innovación generalmente se estudia y se ve reflejada en productos ya sea en forma de bienes o servicios (Donner and de Vries, 2021;Hareebin, 2020). Aunque también pueden encontrarse en los procesos, procedimientos, áreas organizacionales y modelos de negocio (Evans et al, 2017).…”
Section: Innovación Y Sustentabilidad Empresarialunclassified
“…Por su parte el diseño de una política de innovación en beneficio de la sociedad (ambiental y económico) está parcialmente basado en la noción de los tomadores de decisiones, los cuales tienen medidas confiables basados en experiencia y evidencia (London and Sheikh, 2020). Ante esto, la capacidad emprendedora es la etapa principal del desarrollo de innovaciones al emplear los conocimientos y las habilidades para integrar los recursos y alcanzar los objetivos de crecimiento económico y valor agregado (Hareebin, 2020).…”
Section: Innovación Y Sustentabilidad Empresarial Orientada Al Turismounclassified
See 1 more Smart Citation